1998
DOI: 10.1021/jm970644q
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 379. Synthesis of Phenstatin Phosphate1a,

Abstract: A structure-activity relationship (SAR) study of the South African willow tree (Combretum caffrum) antineoplastic constituent combretastatin A-4 (1b) directed at maintaining the (Z)-stilbene relationship of the olefin diphenyl substituents led to synthesis of a potent cancer cell growth inhibitor designated phenstatin (3b). Initially phenstatin silyl ether (3a) was unexpectedly obtained by Jacobsen oxidation of combretastatin A-4 silyl ether (1c --> 3a), and the parent phenstatin (3b) was later synthesized (6a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(158 citation statements)
references
References 32 publications
3
149
2
4
Order By: Relevance
“…It is worth mentioning that this two-step sequence represents a significant improvement over the first hemisynthesis of phenstatin (4 a) from com- bretastatin A4 (3 a) based on Jacobsen's oxidation. [24] The method constitutes a competitive approach to phenstatin and derivatives compared with the PPA-mediated Friedel-Crafts reaction.…”
Section: Synthesis and Characterization Of The Red By-productmentioning
confidence: 99%
“…It is worth mentioning that this two-step sequence represents a significant improvement over the first hemisynthesis of phenstatin (4 a) from com- bretastatin A4 (3 a) based on Jacobsen's oxidation. [24] The method constitutes a competitive approach to phenstatin and derivatives compared with the PPA-mediated Friedel-Crafts reaction.…”
Section: Synthesis and Characterization Of The Red By-productmentioning
confidence: 99%
“…An investigation of the fluoro substitutions revealed that the 3-fluoro derivative (27) exhibited potent cytotoxic activity, and the 2,5-difluoro derivative (29) showed a 5.7-fold increase in potency (IC 50 value= 2.6 nM) compared with compound 7. This may reflect the unique properties of fluorinated organic compounds, including the improved entropies associated with the ligand binding to the target.…”
Section: Modification Of the Alkyl Group On The Imidazole Ringmentioning
confidence: 99%
“…2 Phenstatin (2a) is a synthetic tubulin assembly inhibitor developed by the same research group in 1998. 3 This compound is a benzophenone-type molecule and the functional groups on the two phenyl rings are similar to combretastatin A-4. 4 Based on the structures of both lead compounds, various benzophenone derivatives have been developed including aminobenzophenones (2b-c) 5,6 and isocombretastatin A (3).…”
Section: Introductionmentioning
confidence: 99%
“…A boron atom has a vacant orbital and interconverts with ease between the neutral sp 2 and the anionic sp 3 hybridization states, which generates a new stable interaction between a boron atom and a donor molecule through a covalent bond. 8 Therefore, it is expected that the boron atoms introduced into biologically active molecular frameworks would interact with a target protein not only through hydrogen bonds but also through covalent bonds, and this interaction might produce a potent biological activity.…”
Section: Introductionmentioning
confidence: 99%